Medicinal Chemistry - Thomas, Gareth (John Wiley, 2007)
"Medicinal Chemistry, Second Edition provides a comprehensive, balanced introduction to this evolving, multi-disciplinary subject. The book carefully explains fundamental principles, assuming little in the way of prior knowledge. It opens with a broad overview of medicinal chemistry followed by chapters that cover the principal methods used in drug design and the isolation of drugs from natural sources. Subsequent